Management of hyperthermia with the application of tepid water sponge in pediatric patients with hyperthermia: A case study - Agustina, Winda; Angela, Victoria (Science Center Group, 2024)
Background: Hyperthermia in children with typhoid fever requires timely and safe management because elevated body temperature may increase discomfort, raise metabolic demand, and interfere with recovery. Non-pharmacological measures such as tepid water sponge represent a simple nursing intervention that is feasible and relevant in primary care settings. Objective: To analyze the application of tepid water sponge in the management of hyperthermia among pediatric patients with typhoid fever using a case study approach. Methods: This study used a descriptive case study design involving two pediatric patients aged 5–11 years with typhoid fever and body temperature above 37°C in the working area of UPTD Puskesmas Tanjung Baru from 28 to 31 May 2022. Data were collected through observation, interviews, documentation review, and implementation of the nursing process, including assessment, diagnosis, intervention, implementation, and evaluation. The main intervention was tepid water sponge as part of hyperthermia management. Results: Both patients showed gradual reductions in body temperature over three days of care. In the first case, body temperature decreased from 38.5°C on day 1 to 37.2°C on day 2 and 36.0°C on day 3. In the second case, body temperature decreased from 39.0°C on day 1 to 37.5°C on day 2 and 36.5°C on day 3. Differences in response appeared to be related to the child’s cooperation, medication adherence, fluid intake, and family understanding of hyperthermia management. Conclusion: Tepid water sponge may serve as a supportive nursing intervention to reduce body temperature in children with hyperthermia due to typhoid fever. Its effectiveness should be supported by appropriate monitoring, family education, and active caregiver involvement during care.